2017
DOI: 10.1016/j.jqsrt.2016.09.024
|View full text |Cite
|
Sign up to set email alerts
|

CaH Rydberg series, oscillator strengths and photoionization cross sections from Molecular Quantum Defect and Dyson Orbital theories

Abstract: In this work, electron-propagator methods are applied to the calculation of the ionization potential and vertical excitation energies for several Rydberg series of the CaH molecule.The present calculations cover more highly excited states than those previously reported.In particular, excitation energies for ns (n>5), np (n>5), nd (n>4) and nf Rydberg states are given. Oscillator strengths for electronic transitions involving Rydberg states of CaH, as well as photoionization cross sections for Rydberg channels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…For the rst excited state PECs we employed a technique previously used to estimate the excitation energies of radicals as EBE differences between cation virtual orbitals. [37][38][39][40] In this scheme, virtual positron orbitals are obtained by including ghost positronic basis functions in APMO/ HF calculations for the [X À Y À ] purely electronic system. The APMO/REN-PP3 self-energy corrections are then applied to the second positronic virtual orbital, which allows for estimates of the rst excited state PBE of the e + [X À Y À ] complex.…”
Section: Potential Energy Curvesmentioning
confidence: 99%
“…For the rst excited state PECs we employed a technique previously used to estimate the excitation energies of radicals as EBE differences between cation virtual orbitals. [37][38][39][40] In this scheme, virtual positron orbitals are obtained by including ghost positronic basis functions in APMO/ HF calculations for the [X À Y À ] purely electronic system. The APMO/REN-PP3 self-energy corrections are then applied to the second positronic virtual orbital, which allows for estimates of the rst excited state PBE of the e + [X À Y À ] complex.…”
Section: Potential Energy Curvesmentioning
confidence: 99%
“…All the experimental and theoretical studies for the CaH molecule show the existence of a double well in their excited state 2 ∑ + (Ca(4s4p)+H(1s)), which resulting from an avoided crossing and the existence of the 1 2 Δ state (dissociating into Ca(4s3d)+H(1s)) [33]. Accordingly, numerous studies have been devoted to investigate only the ground and few excited states of this molecule with different approaches (Multireference Configuration Interaction (MRCI), MRCI+Q, CCSD(T)) and various basis sets [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Yadin et al [46] have reported the calculations on rotation-vibration transitions in the ground state of CaH.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, new molecular data for CaH directly associated with electronic transition properties involving Rydberg states have been supplied. Hence, Velasco and co-workers used the MQDO model to calculate the oscillator strengths and photoionization cross sections of calcium monohydride [47]. We present in this paper a theoretical study of the three effective electrons system: CaH molecule based on the pseudo-potential technique and the Core Polarization Potential (CPP).…”
Section: Introductionmentioning
confidence: 99%